Penyelesaian Perkara Kerusakan Tanaman Akibat Perbuatan Melawan Hukum Pemilik Ternak di Kabupaten Bombana Sulawesi Tenggara: Kerusakan Tanaman Akibat Perbuatan Melawan Hukum Pemilik Ternak - Rahman, Irsan; Nurazizah (Pascasarjana Universitas Balikpapan, 2024)
Cattle farming in Bombana Regency is mostly practiced through grazing, which causes social problems in the form of livestock sometimes entering people's gardens and damaging crops. This incident is legally considered as an unlawful act by the livestock owner even though it is not done directly by the livestock owner. On this basis, we conducted research related to how the legal norms of unlawful acts of livestock owners, then how the responsibility of livestock owners and how the settlement of cases of crop destruction by livestock between livestock owners and crop owners. From the results of our research in Bombana Regency, Southeast Sulawesi, we found that in addition to the national legal framework of Articles 1365, 1366, and 1368 of the Indonesian Criminal Code, there are also norms in Regional Regulation No. 4/2017 on the Control of Livestock and the core provisions of the Regional Regulation relating to the obligation of compensation are found in Article 28 Paragraph 1 Letter a. In addition, we found that the responsibility of the owner of the livestock for damaging the crops is the responsibility of the owner of the livestock, In addition, we find that the responsibility for the destruction of crops by livestock is a tort, which is a responsibility due to fault so that the tort can strictly apply the norms mentioned above, the process of resolving cases between livestock owners and crop owners is resolved through non-litigation courts, both negotiation and mediation.